The impact of pneumococcal serotype replacement on the effectiveness of a national immunization program: a population-based active surveillance cohort study in New ZealandResearch in context - Andrew Anglemyer; Xiaoyun Ren; Charlotte Gilkison; Zoe Kumbaroff; Julie Morgan; Kara DuBray; Audrey Tiong; Arthur Reingold; Tony Walls (Elsevier, 2024)
Summary: Background: In Aotearoa New Zealand (NZ) PCV7 was introduced in 2008, then PCV10 in 2011 and PCV13 in 2014. In 2017 PCV10 was re-introduced, replacing PCV13. In the present study, we investigate the resultant rapidly changing invasive pneumococcal disease (IPD) epidemiology. Methods: We compare the IPD incidence rate ratio (IRR) in NZ (2022 versus 2020) with other countries, and describe the IPD epidemiology (including trends in overall IPD and serotype 19A, and antimicrobial resistance) within NZ. Additionally, we performed a genomic-epidemiology investigation identifying the most common 19A sequence types and associated risk factors. Findings: Though IPD incidence rates have increased in the US and Australia (2021-22) after declines in 2020, in NZ the incidence rate is the highest since 2011 with a significantly higher IRR than US (p < 0.01). Incidence rates among children <2 and adults 65 or over in 2022 are the highest since 2009, driven by significant increases of serotype 19A (p = 0.01). Māori and Pacific peoples are experiencing the highest rates since 2009. Further, penicillin resistance among 19A isolates has increased from 39% (2012) to 84% (2021) (p = 0.02). Genomic sequencing identified the more virulent ST-2062 as most common among 19A isolates sequenced, increasing from 5% (2010) to 55% (2022). Interpretation: With very high incidence rates of IPD in NZ, inadequate protection against 19A, increasing resistance, and a more virulent 19A clade, targeted public health campaigns and increased PCV13 availability are needed. Funding: The NZ Ministry of Health funds IPD surveillance and typing in NZ.